2023
DOI: 10.1002/1878-0261.13504
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological NF‐κB inhibition decreases cisplatin chemoresistance in muscle‐invasive bladder cancer and reduces cisplatin‐induced toxicities.

Abstract: Most patients with muscle‐invasive bladder cancer (MIBC) are not cured with platinum chemotherapy. Up‐regulation of nuclear factor kappa light chain enhancer of activated B cells (NF‐κB) is a major mechanism underlying chemoresistance, suggesting that its pharmacological inhibition may increase platinum efficacy. NF‐κB signaling was investigated in two patient cohorts. The Cancer Genome Atlas (TCGA) was used to correlate NF‐κB signaling and patient survival. The efficacy of cisplatin plus the NF‐κB inhibitor d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Further functional experiments in vitro or vivo confirmed that DIAPH3 knockdown could sensitize cisplatin-resistant tumor cells to cisplatin treatment. Moreover, the activation of the NF-kB pathway and EMT pathway have been reported that facilitate the formation of cisplatin resistance [52] , [53] , [54] , [55] , so we explored the relationship between DIAPH3 and these two pathways and found that DIAPH3 knockdown significantly reduced the expression of P-P65, N-cadherin and vimentin. The above results imply that targeting DIAPH3 could be a useful method to reverse cisplatin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Further functional experiments in vitro or vivo confirmed that DIAPH3 knockdown could sensitize cisplatin-resistant tumor cells to cisplatin treatment. Moreover, the activation of the NF-kB pathway and EMT pathway have been reported that facilitate the formation of cisplatin resistance [52] , [53] , [54] , [55] , so we explored the relationship between DIAPH3 and these two pathways and found that DIAPH3 knockdown significantly reduced the expression of P-P65, N-cadherin and vimentin. The above results imply that targeting DIAPH3 could be a useful method to reverse cisplatin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…LCTL gene expression was found to be upregulated in triple-negative breast cancer samples, and expression levels correlated with increased cell proliferation, histological grade, and TNM stage [21]. Bladder cancer includes muscleinvasive and non-muscle-invasive forms [57] with distinct biological behavior. Higher γKlotho protein expression was observed in muscle-invasive versus non-muscle-invasive lesions [22].…”
Section: Clinicopathological Characteristicsmentioning
confidence: 99%